Rekayasa Laba Akrual untuk Meminimalkan Pajak Penghasilan - Siti Munfiah Hidayati; - Khanifah (Universitas Wahid Hasyim, 2006)
The research was held on the background of changes in tax bill which had been stated on Bill Number 17/ 2000 about income tax which was issued since 1 January 2001. The changes of tax bill could make artificial accrual profit for management to minimize income tax with delay profit statement on 2000 period and put this profit to 2001 period.The used data included : net profit, number of fixed active assets, total active assets, changed income, operational cash flow. Used Analytic technique were : classical assume test, multiple regression , t test and mean divert test.The yield of t test and mean divert test could be interpreted that there were no artificial accrual for 2000, and 2001 period to respond the changes of tax bill for minimize income tax.